Pengaruh Implementasi Kebijakan Reformasi Birokrasi Terhadap Efektivitas Organisasi (Suatu Studi Di Sekretariat Daerah Kabupaten Halmahera Utara). - Kori, Olivia Ekstevani; Sondakh, Telly; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: This research dotted from the initial observation that the effectiveness of the organization'sSecretariat indicated area of North Halmahera Regency is still relatively low. This condition is presumablyrelated to policy implementation resformasi bureaucracy that has not gone well. Thus, this study aims: "toanalyze the effect of policy implementation of bureaucratic reforms on the effectiveness of the organization inNorth Halmahera Regional Secretariat".The method used is descriptive method with quantitative approach, the sample of respondents is setpurposively as much as 78 employees. The primary data obtained through the deployment list (questionnaire),while the secondary data obtained through technical documentation. After the data is collected and thenanalyzed by using percentage, followed by testing the hypothesis by using the technique of product momentcorrelation analysis and simple linear regression.The results showed that: Impementasi policy of bureaucratic reform, particularly reform of humanresources in the field of personnel is one of the determining factors (determinants) increasing organizationaleffectiveness. Not optimal achievement of bureaucratic reform, particularly in the Regional Secretariat of NorthHalmahera district with an average of only categorized "medium" performance or the average of 61.9%contributed implicated in not optimal effectiveness of the organization is still in the category of "moderate" tomean achievement average of 69.8%.Statistical analysis showed that between implemntasi bureaucratic reform policy with the effectivenessof the organization has a contributive relationship and a positive linear patterned. Relations between the twovariables is significant at test level of 1%, while the degree of determination (decisive power) of 78.6%.Increase or decrease in the effectiveness of the Regional Secretariat of the organization of North Halmaheradistrict of 78.6 percent determined by bureaucratic reform.Thus, it can be concluded that the results of this study indicate that the hypothesis has been tested byempirical research as well justify the underlying theories. It is recommended that the optimization iplementasipolicy of bureaucratic reform, especially reform of the element of human resources personnel need to be donethrough concrete efforts, such as training and other gina make human resource who has the attitude of integrity,neutral, competent, capable, professional, high-performance and prosperous.Keywords: Bureaucratic reform Apparatus Human resources, organizational effectivenes